Solve for x
x=-\frac{2}{7}\approx -0.285714286
x=1
Graph
Share
Copied to clipboard
6\times 3x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Variable x cannot be equal to -2 since division by zero is not defined. Multiply both sides of the equation by 6\left(x+2\right), the least common multiple of x+2,6.
18x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Multiply 6 and 3 to get 18.
18x-\left(x^{2}+x-2\right)=x\times 6\left(x+2\right)
Use the distributive property to multiply x+2 by x-1 and combine like terms.
18x-x^{2}-x+2=x\times 6\left(x+2\right)
To find the opposite of x^{2}+x-2, find the opposite of each term.
17x-x^{2}+2=x\times 6\left(x+2\right)
Combine 18x and -x to get 17x.
17x-x^{2}+2=6x^{2}+2x\times 6
Use the distributive property to multiply x\times 6 by x+2.
17x-x^{2}+2=6x^{2}+12x
Multiply 2 and 6 to get 12.
17x-x^{2}+2-6x^{2}=12x
Subtract 6x^{2} from both sides.
17x-7x^{2}+2=12x
Combine -x^{2} and -6x^{2} to get -7x^{2}.
17x-7x^{2}+2-12x=0
Subtract 12x from both sides.
5x-7x^{2}+2=0
Combine 17x and -12x to get 5x.
-7x^{2}+5x+2=0
Rearrange the polynomial to put it in standard form. Place the terms in order from highest to lowest power.
a+b=5 ab=-7\times 2=-14
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as -7x^{2}+ax+bx+2. To find a and b, set up a system to be solved.
-1,14 -2,7
Since ab is negative, a and b have the opposite signs. Since a+b is positive, the positive number has greater absolute value than the negative. List all such integer pairs that give product -14.
-1+14=13 -2+7=5
Calculate the sum for each pair.
a=7 b=-2
The solution is the pair that gives sum 5.
\left(-7x^{2}+7x\right)+\left(-2x+2\right)
Rewrite -7x^{2}+5x+2 as \left(-7x^{2}+7x\right)+\left(-2x+2\right).
7x\left(-x+1\right)+2\left(-x+1\right)
Factor out 7x in the first and 2 in the second group.
\left(-x+1\right)\left(7x+2\right)
Factor out common term -x+1 by using distributive property.
x=1 x=-\frac{2}{7}
To find equation solutions, solve -x+1=0 and 7x+2=0.
6\times 3x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Variable x cannot be equal to -2 since division by zero is not defined. Multiply both sides of the equation by 6\left(x+2\right), the least common multiple of x+2,6.
18x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Multiply 6 and 3 to get 18.
18x-\left(x^{2}+x-2\right)=x\times 6\left(x+2\right)
Use the distributive property to multiply x+2 by x-1 and combine like terms.
18x-x^{2}-x+2=x\times 6\left(x+2\right)
To find the opposite of x^{2}+x-2, find the opposite of each term.
17x-x^{2}+2=x\times 6\left(x+2\right)
Combine 18x and -x to get 17x.
17x-x^{2}+2=6x^{2}+2x\times 6
Use the distributive property to multiply x\times 6 by x+2.
17x-x^{2}+2=6x^{2}+12x
Multiply 2 and 6 to get 12.
17x-x^{2}+2-6x^{2}=12x
Subtract 6x^{2} from both sides.
17x-7x^{2}+2=12x
Combine -x^{2} and -6x^{2} to get -7x^{2}.
17x-7x^{2}+2-12x=0
Subtract 12x from both sides.
5x-7x^{2}+2=0
Combine 17x and -12x to get 5x.
-7x^{2}+5x+2=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-5±\sqrt{5^{2}-4\left(-7\right)\times 2}}{2\left(-7\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -7 for a, 5 for b, and 2 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-5±\sqrt{25-4\left(-7\right)\times 2}}{2\left(-7\right)}
Square 5.
x=\frac{-5±\sqrt{25+28\times 2}}{2\left(-7\right)}
Multiply -4 times -7.
x=\frac{-5±\sqrt{25+56}}{2\left(-7\right)}
Multiply 28 times 2.
x=\frac{-5±\sqrt{81}}{2\left(-7\right)}
Add 25 to 56.
x=\frac{-5±9}{2\left(-7\right)}
Take the square root of 81.
x=\frac{-5±9}{-14}
Multiply 2 times -7.
x=\frac{4}{-14}
Now solve the equation x=\frac{-5±9}{-14} when ± is plus. Add -5 to 9.
x=-\frac{2}{7}
Reduce the fraction \frac{4}{-14} to lowest terms by extracting and canceling out 2.
x=-\frac{14}{-14}
Now solve the equation x=\frac{-5±9}{-14} when ± is minus. Subtract 9 from -5.
x=1
Divide -14 by -14.
x=-\frac{2}{7} x=1
The equation is now solved.
6\times 3x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Variable x cannot be equal to -2 since division by zero is not defined. Multiply both sides of the equation by 6\left(x+2\right), the least common multiple of x+2,6.
18x-\left(x+2\right)\left(x-1\right)=x\times 6\left(x+2\right)
Multiply 6 and 3 to get 18.
18x-\left(x^{2}+x-2\right)=x\times 6\left(x+2\right)
Use the distributive property to multiply x+2 by x-1 and combine like terms.
18x-x^{2}-x+2=x\times 6\left(x+2\right)
To find the opposite of x^{2}+x-2, find the opposite of each term.
17x-x^{2}+2=x\times 6\left(x+2\right)
Combine 18x and -x to get 17x.
17x-x^{2}+2=6x^{2}+2x\times 6
Use the distributive property to multiply x\times 6 by x+2.
17x-x^{2}+2=6x^{2}+12x
Multiply 2 and 6 to get 12.
17x-x^{2}+2-6x^{2}=12x
Subtract 6x^{2} from both sides.
17x-7x^{2}+2=12x
Combine -x^{2} and -6x^{2} to get -7x^{2}.
17x-7x^{2}+2-12x=0
Subtract 12x from both sides.
5x-7x^{2}+2=0
Combine 17x and -12x to get 5x.
5x-7x^{2}=-2
Subtract 2 from both sides. Anything subtracted from zero gives its negation.
-7x^{2}+5x=-2
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-7x^{2}+5x}{-7}=-\frac{2}{-7}
Divide both sides by -7.
x^{2}+\frac{5}{-7}x=-\frac{2}{-7}
Dividing by -7 undoes the multiplication by -7.
x^{2}-\frac{5}{7}x=-\frac{2}{-7}
Divide 5 by -7.
x^{2}-\frac{5}{7}x=\frac{2}{7}
Divide -2 by -7.
x^{2}-\frac{5}{7}x+\left(-\frac{5}{14}\right)^{2}=\frac{2}{7}+\left(-\frac{5}{14}\right)^{2}
Divide -\frac{5}{7}, the coefficient of the x term, by 2 to get -\frac{5}{14}. Then add the square of -\frac{5}{14} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{5}{7}x+\frac{25}{196}=\frac{2}{7}+\frac{25}{196}
Square -\frac{5}{14} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{5}{7}x+\frac{25}{196}=\frac{81}{196}
Add \frac{2}{7} to \frac{25}{196} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x-\frac{5}{14}\right)^{2}=\frac{81}{196}
Factor x^{2}-\frac{5}{7}x+\frac{25}{196}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{5}{14}\right)^{2}}=\sqrt{\frac{81}{196}}
Take the square root of both sides of the equation.
x-\frac{5}{14}=\frac{9}{14} x-\frac{5}{14}=-\frac{9}{14}
Simplify.
x=1 x=-\frac{2}{7}
Add \frac{5}{14} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}